Conventional Fiscal Policy System and Islamic Economics in The Indonesian Economy - Kadir, Syahruddin; Fahrika, A. Ika; Misbach, Irwan (Widya Cipta - Jurnal Sekretari dan Manajemen, 2024)
The economic crisis and political turmoil in the 1990s did not guarantee the strength of Indonesia's economic situation, therefore political and fiscal decentralization was initiated and Law No. 25 was passed in 1999. This research aims to understand conventional fiscal policy and Islamic economics in the Indonesian economy. This research method uses literature study through secondary data collection. The results of this research show that conventional fiscal policy has a stability function that aims to, among other things, maintain high employment opportunities, relatively stable price levels, and economic growth rates. This function shows the similarity of the functions and benefits of zakat, jizyah, khums, and kharaj in Islamic economic fiscal policy. If zakat, jizyah, khums, and kharaj are instruments of fiscal policy, the redistribution of income and wealth will take place, then the problem of poverty and economic growth can be reduced and will have a good impact on economic and political stability. According to experts, the concept of contractionary fiscal policy is reducing government spending so that the money supply can be reduced through income redistribution. This is in line with the aim of fiscal policy instruments in Islamic economics to improve the living standards of the poor by redistributing the income of the rich to the poor.